2008
DOI: 10.2967/jnumed.108.056051
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Left Ventricular Volumes and Ejection Fraction in Mice Using PET, Compared with MRI

Abstract: PET has become an important noninvasive imaging technique in cardiovascular research for the characterization of mouse models in vivo. This modality offers unique insight into biochemical changes on a molecular level, with excellent sensitivity. However, morphologic and functional changes may be of equal importance for a thorough assessment of left ventricular (LV) pathophysiology. Although echocardiography and MRI are widely considered the imaging techniques of choice for the assessment of these parameters, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 27 publications
6
35
1
Order By: Relevance
“…Quantification of segmental tracer uptake and volumes of the left ventricle were performed using a contour-detection algorithm developed in-house and validated against MRI (13). Here, the left ventricle was segmented into 8 segments per short-axis plane, with 7 planes per heart, resulting in 56 segments.…”
Section: Pet Imagingmentioning
confidence: 99%
“…Quantification of segmental tracer uptake and volumes of the left ventricle were performed using a contour-detection algorithm developed in-house and validated against MRI (13). Here, the left ventricle was segmented into 8 segments per short-axis plane, with 7 planes per heart, resulting in 56 segments.…”
Section: Pet Imagingmentioning
confidence: 99%
“…Cardiopulmonary status, including right ventricular function, pulmonary vascular function, and right ventricular-pulmonary vascular interactions, is an important facet of health and disease. Recently, different methods for assessing left ventricular function, systemic vascular function, and the efficiency of left ventricular-systemic vascular hemodynamic interactions in mice in situ have been described (13,16,17,39,41,47,53,54,64). However, the feasibility and utility of these techniques in the right ventricle and pulmonary vasculature of mice have not been established.…”
mentioning
confidence: 99%
“…The explanation of a lower resolution as the main reason for the underestimation of LV volumes and overestimation of EF is supported when the results are compared with the results of the high-resolution scanner. However, between high-resolution PET and MR images, there are remaining discrepancies in EDV and ESV that were not observed in a previous study using a similar setup and the same contourfinding algorithm (18).…”
Section: Discussionmentioning
confidence: 56%
“…Even though most of the destruction of myocardium and subsequent structural changes have already taken place in the time between the surgery and first imaging study, as has been shown by Lutgens et al (22), residual changes may have taken place between the combined PET/MRI and the dedicated PET acquisitions. Second, the software used for MRI contour detection in the study by Stegger et al (18) was not accessible for this study, and contours were traced manually instead, leading to additional systematic deviances on the MRI side. Thus, the high-resolution PET images do not necessarily correlate with the MR images exactly as has been observed before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation